2015
DOI: 10.7314/apjcp.2015.16.10.4147
|View full text |Cite
|
Sign up to set email alerts
|

Current Drugs and Drug Targets in Non-Small Cell Lung Cancer: Limitations and Opportunities

Abstract: Lung cancer is a serious health problem and leading cause of death worldwide due to its high incidence and mortality. More than 80% of lung cancers feature a non-small cell histology. Over few decades, systemic chemotherapy and surgery are the only treatment options in this type of tumor but due to their limited efficacy and overall poor survival of patients, there is an urge to develop newer therapeutic strategies which circumvent the problems. Enhanced knowledge of translational science and molecular biology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 102 publications
(66 reference statements)
0
34
0
Order By: Relevance
“…Approximately 80% of all lung cancer cases are non-small cell lung cancer (NSCLC) (10,11) and the majority of patients have been diagnosed in the advanced stage (12). At present the primary method for clinical treatment of advanced NSCLC is drug treatment, including chemotherapy and biological therapy (which may involve tumor specific monoclonal antibodies, molecular targeted drugs or antiangiogenic drugs).…”
Section: Cytokine-induced Killer Cell Therapy For Modulating Regulatomentioning
confidence: 99%
“…Approximately 80% of all lung cancer cases are non-small cell lung cancer (NSCLC) (10,11) and the majority of patients have been diagnosed in the advanced stage (12). At present the primary method for clinical treatment of advanced NSCLC is drug treatment, including chemotherapy and biological therapy (which may involve tumor specific monoclonal antibodies, molecular targeted drugs or antiangiogenic drugs).…”
Section: Cytokine-induced Killer Cell Therapy For Modulating Regulatomentioning
confidence: 99%
“…Lung cancer-related death is primarily due to complexity in the molecular biology of the disease, resulting in drug resistance and metastasis [6]. Therefore, it is imperative to understand the molecular signaling involved in lung carcinogenesis and to identify new therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer remains the leading cause of cancer-related death worldwide, despite extensive advances made in treatment approaches [1][2][3][4][5]. Drug resistance and metastasis make effective treatment strategies difficult [6]. Several ongoing studies into the molecular basis of lung cancer have shown that various signaling pathways are deregulated during the tumorigenic process and are involved in the resistance of cancer cells to existing therapies [7].…”
Section: Introductionmentioning
confidence: 99%
“…Patients burdened with large size tumors usually have poor clinical prognosis. Even though new drugs targeting various critical oncogenes significantly reduce tumor size before surgery, side-effects seriously restrict the effective clinical application of these drugs (2). Thus, the identification of new therapeutic targets remains vital for effective NSCLC treatment.…”
Section: Introductionmentioning
confidence: 99%